Phytochemical Investigations of the Pollens of Prosopis juliflora - VYAS, GOVERDHAN; AGARWAL, M.M.; PANDEY, H.K.; BHOJAK, N. (Asian Journal of Chemistry, 2010)
In this work, the amino acids contents in the pollens of Prosopis juliflora have been analyzed.